Rice Plants’ Resistance to Sheath Blight Infection Is Increased by the Synergistic Effects of Trichoderma Inoculation with SRI Management - Febri Doni; Anizan Isahak; F. Fathurrahman; Wan Mohtar Wan Yusoff (Agronomy, 2023)
The capability of endophytic Trichoderma spp. to reduce sheath blight disease in rice caused by Rhizoctonia solani was assessed under the growth conditions established by practices of the System of Rice Intensification (SRI), compared to those of standard irrigated rice cultivation. Rice seeds inoculated with a local isolate of the fungus Trichoderma asperellum SL2 were grown under respective SRI and conventional conditions with the inoculated or uninoculated plants and then infected with the pathogen R. solani. It was seen that inoculation with this strain of Trichoderma protected rice plants against R. solani infection while enhancing plant growth, photosynthetic rate, and stomatal conductance. The biocontrol effectiveness of inoculation with a particular strain of Trichoderma was significantly greater under SRI management compared to conventional cultivation. This is the first report on how a crop management system, in this case, SRI, can influence the biocontrol effectiveness of Trichoderma spp.